Economic Impact of Tourism on Local Communities in Gashaka Gumti National Park - Silas, Akafa Konde; Madaki, Kanati; Chibuma, Gani Saidu (Kwaghe International Journal of Arts, Humanities and Religious Studies, 2025)
Gashaka Gumti National Park, located across Taraba and Adamawa States along the Cameroon border and home to diverse grasslands and Nigeria’s highest peak, Chappal Waddii (“Mountain of Death”), serves as a critical site for tourism and conservation. This study analyzes the factors influencing the economic impact of tourism on local communities within the park. It hypothesizes that employment in tourism increases community participation in biodiversity conservation, that financial benefits directly affect the likelihood of engaging in conservation activities, and that infrastructure development enhances household willingness to support conservation efforts. Data were collected through household questionnaires and analyzed using logistic regression. The findings support all three hypotheses, demonstrating that tourism generates significant economic impacts that positively shape local engagement in conservation. This study adds to empirical evidence on the nexus between tourism, livelihoods, and conservation, and underscores the importance of designing tourism strategies that maximize local economic benefits. The results carry practical implications for park managers and policymakers, particularly in strengthening community–park relations and promoting sustainable conservation practices.